Mountain futures: pursuing innovative adaptations in coupled social–ecological systems - Grumbine, R. Edward; Xu, J.C. (Wiley, 2021)
Covering about 12.5% of the Earth’s terrestrial surface, mountains have great value for people and nature. They provide habitat for one-third of terrestrial species diversity, have irreplaceable cultural and spiritual worth to humans, and are a source of fresh water for nearly 2 billion people. To date, progress on meeting policy goals to protect mountain systems has been slow; however, in 2019, several major reports on the contributions alpine environments make to life on Earth were produced by international agencies. These reports call for transformative change in decision making to address problems of sustainability in mountain ecosystems. We consider prospects for such change by reviewing several international partnerships focused on mountains. We then spotlight the Mountain Futures Initiative, which provides multiple examples of innovative local/regional research that give special focus to linking science with local livelihood support. Communities in alpine regions will continue to require assistance if they are to adapt to the environmental and social shifts characteristic of life in the Anthropocene.